2010
DOI: 10.1186/1475-2875-9-101
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-tocopherol transfer protein disruption confers resistance to malarial infection in mice

Abstract: BackgroundVarious factors impact the severity of malaria, including the nutritional status of the host. Vitamin E, an intra and extracellular anti-oxidant, is one such nutrient whose absence was shown previously to negatively affect Plasmodium development. However, mechanisms of this Plasmodium inhibition, in addition to means by which to exploit this finding as a therapeutic strategy, remain unclear.Methodsα-TTP knockout mice were infected with Plasmodium berghei NK65 or Plasmodium yoelii XL-17, parasitaemia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 37 publications
(44 reference statements)
0
30
0
1
Order By: Relevance
“…After probucol treatment for 2 weeks, a subgroup of the treated mice was fed with a standard diet for 2 weeks. Blood samples were obtained under anesthesia with diethyl ether (Wako; Tokyo, Japan) by cardiac puncture using sodium citrate (Wako; Tokyo, Japan) as an anticoagulant, and then blood samples were centrifuged at 5000 rpm for 5 min at 4°C to remove the plasma and buffy coat [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After probucol treatment for 2 weeks, a subgroup of the treated mice was fed with a standard diet for 2 weeks. Blood samples were obtained under anesthesia with diethyl ether (Wako; Tokyo, Japan) by cardiac puncture using sodium citrate (Wako; Tokyo, Japan) as an anticoagulant, and then blood samples were centrifuged at 5000 rpm for 5 min at 4°C to remove the plasma and buffy coat [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have reported that α-tocopherol transfer protein knockout (α-ttp Δ ) mice showing undetectable plasma concentrations of α-tocopherol, the most biologically active form of vitamin E, were resistant against malaria and cerebral malaria [ 21 ]. This resistance was attributed to the parasite DNA damage derived from the high oxidative stress due to α-tocopherol deficiency [ 22 ]. We have also demonstrated that this protective effect can be reversed by feeding α-ttp Δ mice with α-tocopherol-supplemented diets [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Donor BALB/c mice were intraperitoneally injected with 1×10 6 erythrocytes infected with P. yoelii 17XL strain [19,20]. Parasitaemia was monitored by counting the number of parasite-infected erythrocytes per 1,000 erythrocytes by microscopic examination of Giemsa-stained, thin (tail) blood smears.…”
Section: Methodsmentioning
confidence: 99%
“…[22][23][24] Mice which lack the α-TTP liver cytosolic protein and which have very little vitamin E in circulation are highly resistant against malaria. 25 The consumption of foods rich in vitamin E like peanut butter or moringa has probably to be reduced to avoid malaria infections. The same probably applies to vegetable oils rich in vitamin E or even vegetable gelatin capsules where at the Worcester Polytechnic Institute it was found that these food components significantly decrease the recovery of artemisinin, a strong oxidant, from the intestinal liquid phase, but not those of flavonoids.…”
Section: Vitamin Ementioning
confidence: 99%